"WHITE TRASH": GESTURES AND PROFANATIONS IN THE VISUAL ECONOMY OF FASHION. Issue 1 (1st January 2021) - Filippello, Roberto
ABSTRACT: In this article, a photo story depicting "white trash" subjects in the act of defying middle-class proprieties of dress and manners serves as a case study for a critical exploration of the performative registers through which working-class bodies figure as agents of social sedition in the visual economy of fashion. The unglamorous and confrontational bodies in Memory —shot by Alexei Hay and Justine Parsons for Dutch in 2000—enact a parody of professional fashion models by exhibiting an exuberant, uncontained sexuality that cuts against the codes of "good taste" and decorum. The photo spread epitomizes how the vernacular aesthetic of "white trash" has been embraced by independent fashion magazines in order to unsettle the normative aesthetics associated with high fashion imagery and, more broadly, mainstream visual culture. Engaging with Giorgio Agamben's reflections on gesture and profanation, the article discusses the political effect of an overperformance of corporeality through prosaic, bawdy gestures and argues that the unboundedness of the bodies in the photo spread represents an affront to the capitalist regime of productivity from which these bodies are excluded. Finally, it highlights the contribution of the aesthetic category of "white trash" to the troubling of the representational conventions within the genre of editorial fashion photography and calls for a politically committed rethinking of the aesthetic consumption of fashion images.